1995
DOI: 10.1111/j.1349-7006.1995.tb03010.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Kampo Medicines and Baicalin against Intestinal Toxicity of a New Anticancer Camptothecin Derivative, Irinotecan Hydrochloride (CPT‐11), in Rats

Abstract: In clinical use, irinotecan hydrochloride (CPT‐11; 7‐ethyl‐10‐[4‐(piperidmo)‐l‐piperidino]carbonyl‐oxycamptothecin), a novel antitumor agent, causes a relatively high incidence of severe forms of diarrhea. We investigated whether baicalin, an inhibitor of β‐glucuronidase, which deconjugates the glucuronide of the active metabolite of CPT‐11, SN‐38 (7‐ethyl‐10‐hydorxycamptothecin), and Japanese herbal medicines (Kampo medicines) which contain baicalin can ameliorate CPT‐11‐induced intestinal toxicity in rats. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 14 publications
2
73
0
Order By: Relevance
“…Furthermore, in a preliminary study, Fittkau et al (2004) did not confirm the anti-diarrhoeal activity of D-saccharic acid 1.4-lactone (a specific b-glucuronidase inhibitor), although Wallace et al (2010) showed an opposite result by oral administration of an inhibitor of the enzyme, which protected mice from irinotecan-induced toxicity. Takasuna et al (1996) also showed that inhibition of the b-glucuronidase activity of the intestinal microbiota could be the major protective mechanism of antibiotics. Thus, the relationship between b-glucuronidase activity and mucositis is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in a preliminary study, Fittkau et al (2004) did not confirm the anti-diarrhoeal activity of D-saccharic acid 1.4-lactone (a specific b-glucuronidase inhibitor), although Wallace et al (2010) showed an opposite result by oral administration of an inhibitor of the enzyme, which protected mice from irinotecan-induced toxicity. Takasuna et al (1996) also showed that inhibition of the b-glucuronidase activity of the intestinal microbiota could be the major protective mechanism of antibiotics. Thus, the relationship between b-glucuronidase activity and mucositis is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…After its action, SN-38 is inactivated by glucuronidation by the uridine diphosphate glucoronosyltransferase 1A1 (UGT1A1) and eliminated in the bile as its glucuronidated form SN-38G (Sparreboom et al, 1998). However, this inactivated form might be re-activated in the intestine if bacteria producing b-glucuronidase are present in the local microbiota (Takasuna et al, 1996), although, in CV animals, most of the SN-38 produced from SN-38G by action of b-glucuronidase is rapidly adsorbed on the bacteria cell wall or intestinal dietary fibre, so that only 10 % remains in the unbound form that can be measured in the intestinal fluid (Takakura et al, 2012). This could explain, in part, the paradoxical higher levels of SN-38 observed in the intestinal luminal fluid of GF mice.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with the tolerance in mice. Progresses in overcoming CPT-11 toxicity in humans should improve the clinical use of this compound (Takasuna et al, 1995(Takasuna et al, , 1996. Nevertheless, even at the moderate doses tolerable by human hosts, top1 inhibitors are active agents in patients with metastatic colorectal cancers (Conti et al, 1996;Pazdur et al, 1997) and reviewed in Rougier and Bugat (1996);Rothenberg (1997).…”
Section: Discussionmentioning
confidence: 99%
“…Since SN-38G, once excreted in the intestinal lumen, is extensively hydrolyzed by bacterial ß-glucuronidase to free SN-38, it was thought that direct intestinal damage by the free intestinal luminal SN-38 was responsible for the delayed-onset diarrhea. Takasuna et al (10,18) reported on the good correlation between the fecal concentration of SN-38 and the anatomic damage of the intestinal mucosa in mice, as well as a greater degree of histological damage in the intestinal segments where the bacterial ß-glucuronidase activity was prominent (caecum and colon). However, our knowledge of the precise mechanism involved in the latter is far from complete.…”
Section: Discussionmentioning
confidence: 99%
“…SN-38G is the inactive metabolite and is secreted in the duodenum (5-7). Many authors consider that the intestinal bacterial microflora are responsible for the damage to the intestinal mucosa, because intestinal bacterial ß-glucuronidase can deconjugate SN-38G into active SN-38, which causes mucosal damage in the small intestine thus causing toxic diarrhea (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%